Effect of hydropriming and various level of plant growth regulator, salicylic acid (SA), and 2.4.D and benzyl aminopurin (BA) on seed deterioration repair of Hairy Vetch (Vicia villosa) and Bitter Vetch (Vicia ervilia - سمانه عبادتی; محمد انتصاری; ناصر مجنون حسینی; حسین مقدم (علوم و فناوری بذر ایران)
During seed storage, some seeds traits might change and seed vigor may decrease in bad storage situation, to determine the effect of some hormones in different concentrations, the study was conducted in biotechnology laboratory of Agriculture University of Tehran in 2012. In this study, seeds aging were tested for 0, 2 and 4 days and after they were primed with distilled water, salicylic acid, IAA and kinetin. Traits measured included germination percent, germination rate, shoot length, root length, seedling dry matter and vigor. The results showed that hydro priming improved many characteristics in fresh seeds but it's not very useful for seeds under ageing conditions. For rising seed vigor in these cases, it's better to use hormones, especially salicylic acid which is called tolerant hormone. Using IAA because of broadleaf control property, it doesn’t seem logically. The best treatment in this study was salicylic acid in low concentration